2015
DOI: 10.1002/ldr.2366
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Performance of the Restored South East New Territories (SENT) Landfill in Hong Kong (2000–2012)

Abstract: South East New Territories (SENT) landfill (Phase I) was saturated with wastes and capped with a cover system to prevent rainfall infiltration and gas emission and to support plant growth. Subsequently, a revegetation program was conducted in 1997. Line transects were used for monitoring (i) the restored area (AT), (ii) the area adjacent to AT (BT) and (iii) the area outside AT, which served as control (CT). Flora and fauna diversities, plant performance (chlorophyll florescent and stomatal resistance of Acaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…Land degradation caused by human activities has significant adverse effects on the environments and ecosystems worldwide (Thomaz and Luiz, 2012;Bai et al, 2013;Li et al, 2013;Chen et al, 2015), and solid waste is an important and emerging environmental problem. It was estimated that 0.5-4.5 kg per person per day of solid waste is produced in different regions of the world (Bakare et al, 2005;Swati et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Land degradation caused by human activities has significant adverse effects on the environments and ecosystems worldwide (Thomaz and Luiz, 2012;Bai et al, 2013;Li et al, 2013;Chen et al, 2015), and solid waste is an important and emerging environmental problem. It was estimated that 0.5-4.5 kg per person per day of solid waste is produced in different regions of the world (Bakare et al, 2005;Swati et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Contamination of soils by heavy metals is now widespread (AlNagger et al, 2013). Land degradation caused by heavy metals has significant adverse effects on the environment and ecosystem worldwide (Li et al, 2013;Chen et al, 2015). Dispersion of heavy metals in irrigated soils and the plants that are growing results in the contamination of food that may be hazardous to humans and animals (Jolly et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Restoration of sanitary and non-sanitary landfills is necessary to minimize adverse impacts on the environment (Do et al, 2013). To provide scientific data for future restoration management, Chen et al (2015) compared the ecological performances between natural sites and revegetated landfill sites and showed that, during the study period, there was a gradual change in the plant communities at restored sites and an increase in biodiversity. Research has also shown that exotic plant species may be more suitable for use as pioneer species in the restoration of sanitary landfills (Wong et al, 2015b) and also pioneer native species were much better than other native species (Wong et al, 2015a).…”
Section: Resultsmentioning
confidence: 99%